2018
DOI: 10.1002/bit.26813
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamic modeling of alternating tangential flow filtration for perfusion cell culture

Abstract: Alternating tangential flow (ATF) filtration has been successfully adopted as a low shear cell separation device in many perfusion‐based processes. The reverse flow per cycle is used to minimize fouling compared with tangential flow filtration. Currently, modeling of the ATF system is based on empirically derived formulas, leading to oversimplification of model parameters. In this study, an experimentally validated porous computational fluid dynamic (CFD) model was used to predict localized fluid behavior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Contrary to runs 1 and 2, the concentration of the product was not equal in the bioreactor and in the harvest stream. This gradient is referred to as sieving and occurs when the membrane permeability is decreasing 38,39 . High cell densities or addition of antifoam agents are suspected to largely contribute to this effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to runs 1 and 2, the concentration of the product was not equal in the bioreactor and in the harvest stream. This gradient is referred to as sieving and occurs when the membrane permeability is decreasing 38,39 . High cell densities or addition of antifoam agents are suspected to largely contribute to this effect.…”
Section: Resultsmentioning
confidence: 99%
“…This gradient is referred to as sieving and occurs when the membrane permeability is decreasing. 38,39 High cell densities or addition of antifoam agents are suspected to largely contribute to this effect. Figure 8 summarizes the different performances that were obtained in this study.…”
Section: Pushing Toward Higher Cell Densitiesmentioning
confidence: 99%
“…Critically, the cell culture performance was not compromised despite the reduced permeate rate. The importance of minimizing filter fouling is relevant not only in perfusion seed cultures, but also production processes to maintain the desired product retention 27,28 . Kim et al demonstrated the need to control the TMP of hollow fiber filters to reasonable levels in order to enhance FVIII yield of their perfusion culture 5 .…”
Section: Discussionmentioning
confidence: 99%
“…23 We demonstrated through experimentation at small scale that the high TMP observed in our perfusion process is predominantly driven by reversible fouling that is likely an but also production processes to maintain the desired product retention. 27,28 Kim et al demonstrated the need to control the TMP of hollow fiber filters to reasonable levels in order to enhance FVIII yield of their perfusion culture. 5 The reduction in the permeate flow rate at manufacturing scale also resulted in an overall savings of 15% of the perfusion medium required to maintain the 5 days N-1 operation.…”
Section: Parameter Impact On Reversible Foulingmentioning
confidence: 99%
“…Likewise, fast inversions of the feed flow direction, as described for ATF systems, can be applied. Thereby, membrane sections along the fiber change periodically the flow direction across the membrane facilitating continuous backflushing with each pump cycle (Radoniqi, Zhang, Bardliving, Shamlou, & Coffman, 2018;Figure 1). Although these hydraulic cleaning methods can be effective, they may increase the shear stress on cells and reduce the net flux.…”
Section: Introductionmentioning
confidence: 99%